2021
DOI: 10.37689/acta-ape/2021ao02851
|View full text |Cite
|
Sign up to set email alerts
|

Marcadores da autopercepção positiva de saúde de pessoas idosas no Brasil

Abstract: Marcadores da autopercepção positiva de saúde de pessoas idosas no Brasil Positive self-perceived health markers in the older adult population in Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
1
2
1
5
Order By: Relevance
“…As other studies 8,24 , the present one also found lower prevalences of positive SPH in those who self-reportedas blacks or browns, with plausible results due to the historical and social inequalities that still persist between black and white people in the Brazilian context, and it is more evident in the population with fewer years of education.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As other studies 8,24 , the present one also found lower prevalences of positive SPH in those who self-reportedas blacks or browns, with plausible results due to the historical and social inequalities that still persist between black and white people in the Brazilian context, and it is more evident in the population with fewer years of education.…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to some studies carried out 8,29 no associations were found with smoking, but associations were found between the regular consumption of fruits and vegetables and the sufficient practice of physical activity during leisure time in women, behavioral variables whose importance and relationship with SPH are already well presented in the literature. 21,[30][31][32] .…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Estudos envolvendo a AS com a população idosa têm utilizado tal medida com a finalidade de compreender os fatores relacionados ao envelhecimento saudável e ao bem-estar 1, 3,5 . Essas pesquisas têm observado importantes associações da AS com a presença de morbidades 7,8 , estilo de vida 8,9 e a participação social 10,11 .…”
Section: Introductionunclassified